Aminoclay–lipid hybrid composite as a novel drug carrier of fenofibrate for the enhancement of drug release and oral absorption - Yang L (Dove Medical Press, 2016)
Liang Yang, Yating Shao, Hyo-Kyung Han BK Plus Project Team, College of Pharmacy, Dongguk University, Goyang, South Korea Abstract: This study aimed to prepare the aminoclay–lipid hybrid composite to enhance the drug release and improve the oral bioavailability of poorly water-soluble fenofibrate. Antisolvent precipitation coupled with an immediate freeze-drying method was adopted to incorporate fenofibrate into aminoclay–lipid hybrid composite (ALC). The optimal composition of the ALC formulation was determined as the ratios of aminoclay to krill oil of 3:1 (w/w), krill oil to fenofibrate of 2:1 (w/w), and antisolvent to solvent of 6:4 (v/v). The morphological characteristics of ALC formulation were determined using scanning electron microscopy, differential scanning calorimetry, and X-ray powder diffraction, which indicated microcrystalline state of fenofibrate in ALC formulation. The ALC formulation achieved almost complete dissolution within 30 minutes, whereas the untreated powder and physical mixture exhibited less than 15% drug release. Furthermore, ALC formulation effectively increased the peak plasma concentration (Cmax) and area under the curve (AUC) of fenofibric acid (an active metabolite) in rats by approximately 13- and seven-fold, respectively. Furthermore, ALC formulation exhibited much lower moisture sorption behavior than the lyophilized formulation using sucrose as a cryoprotectant. Taken together, the present findings suggest that ALC formulation is promising for improving the oral absorption of poorly soluble fenofibrate. Keywords: aminoclay, omega-3 phospholipids, fenofibrate, drug release, oral absorption